Democracy's guardians : a history of the German Federal Constitutional Court 1951-2001 - Collings, Justin (Oxford, United Kingdom : Oxford University Press, 2015)
"In its six-decade history, the German Federal Constitutional Court has become one of the most powerful and influential constitutional tribunals in the world. It has played a central role in the establishment of liberalism, democracy, and the rule of law in post-war West Germany, and it has been a model for constitutional tribunals in many other nations. The Court stands virtually unchallenged as the most trusted institution of the German state. A complex history of the German Federal Constitutional Court from its founding it 1951 up into the twenty-first century, this book explores how the court became so powerful, and why so few can resist its strengths. Through a comprehensive narrative of the Court's remarkable rise and careful analysis of its periodic crises, the work carefully dissects the success of the Court, presenting not only a traditional work of legal history, but a public history - both political and societal - as well as a doctrinal and jurisprudential account. Structured around the Court's major decisions from 1951 to 2001, the book examines popular and political reactions to those decisions, drawing heavily on newspaper accounts of major judgments and material from the archives of individual politicians and judges. The result is an impressive case study of the global phenomenon of constitutional justice"--Unedited summary from book jacket.
Consolidation, 1951-1959 -- Confidence, 1959-1971 -- Confrontation, 1971-1982 -- Continuity, 1982-1990 -- Karlsruhe Republic, 1990-2001 -- Epilogue: the view from Europe.
Based on the author's thesis (doctoral)--Yale University, 2013.
Includes bibliographical references (pages 307-321) and index.
Keywords: Germany. -- Bundesverfassungsgericht -- History; Germany. -- Bundesverfassungsgericht; Constitutional courts; Constitutional courts -- Germany; Germany; History